The Relationship of Mother's Knowledge about Dental Caries and Mother's Behavior in Preventing Dental Careies in Children - Pujianti, Linda; Mukminin, Amirul (Jurusan PGPAUD FIP UNNES, 2024)
The purpose of this study was to determine the relationship between mother's knowledge of dental caries and mother's behavior in preventing dental caries in children (research at PAUD Institute in Sojomerto Village). This research method is quantitative with the research approach used is cross sectional. Data collection techniques using a questionnaire or a questionnaire using a simple random sampling technique. The respondents involved were 61 mothers who have children who attend PAUD institutions in Sojomerto village. This study uses a data analysis technique in the form of Spearman's Rank to determine the relationship between the two variables. The results showed that the average value of the independent variables was 22.36 which was included in the category of moderate knowledge. While the average value of the dependent variable has a score of 108 which is in the good enough category for maternal behavior in preventing dental caries in children. Based on the data analysis test, there was a significant relationship between mother's knowledge about dental caries and mother's behavior in preventing dental caries in children (research at PAUD Institute in Sojomerto Village). The results of the Spearman Rank test show that the P value is 0.000. This means that P Value <0.005 (0.000 <0.005) which means Ha is accepted and Ho is rejected. Where Ha reads